Altaic Elements in the Chinese Variety of Tangwang: True and False Direct Loans - Julie Pauline Marie Lefort (Languages, 2024)
This paper foccusses on the Tangwang language, a Chinese variety spoken in southern Gansu that has been in contact with the Dongxiang language, a Mongolic language. Tangwang is believed to be a highly altaicised variety, as it demonstrate several traits that are usually absent in this language family are are reputed ‘typical’ of the Turkic-Mongolic languages. However, most of these traits are present in the other northwestern chinese varieties and are the result of reanalysis, thus, it is difficult to trace their exact origin. This paper aims at analyzing the influence of Mongolic languages on Tangwang from the perspective of borrowings, and in particular direct loans. Taking the formally identical features that are shared in Dongxiang and Tangwang as a starting point, we will try to determine which form can be seen as a direct borrowing due to the adstratal influence of Dongxiang and which one is probably due to an earlier altaic influence. We will try to classify which form is a ‘true’ direct loan from Dongxiang and which form could be the evidence of an earlier substrate. From the results, and based on the existing models on languages contact, we will try to understand which mechanisms from relexification, grammaticalization, and language shift is the most probable in the case of Tangwang.